KADAR AIR DAN TOTAL BAKTERI DAGING KAMBING YANG DIBERI ASAP CAIR TONGKOL JAGUNG DAN TEMPURUNG KELAPA - Mokmin Mokmin; Wahyu Mushollaeni; Budi Santosa (Journal of Food Technology and Agroindustry dipublikasikan oleh Universitas Wiraraja, 2019)
Corn cobs and coconut shell are a type of waste that can be used as a raw material of to produce liquid smoke. The reseach used randomized block design two factors which fisrt factor is a type of liquid smoke (corn cobs, coconuts shell) and the second factor is liquid smoke concentration (1%, 1.5%, 2.0%, 2.5%). The parameters experiment include are water content and total bacteria (TPC)of the lamb. The result showed of treatment has not significant effect of water content of lamb and the concentration liquid smoke of the corn cobs and liquid smoke of the coconut shell significant effect to total bacteria of lamb. The lowest total bacteria on treatment liquid smoke of corn cobs with concentration 2.5% that is showed 1.5x107cfu/g lamb.